2007
DOI: 10.3892/or.17.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle regulating proteins p21 and p27 in prognosis of oral squamous cell carcinomas

Abstract: Abstract. Cyclin-dependent kinases (CDKs) and cyclindependent kinase inhibitors (CDKIs), such as p21 and p27, exert a direct control on the cell cycle. p21 and p27 are negative regulators of cyclin-dependent kinases and in this function they are negative check-point regulators of the cell cycle. We therefore aimed to evaluate p21 and p27 expression in oral squamous cell carcinomas (OSSC) to determine the value as a prognostic marker. One hundred and ninety-two patients with histologically proven, surgically tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 18 publications
6
58
1
1
Order By: Relevance
“…17 In the current study, we found PKM2 could interact with p27, and decreased level of p27 in PKM2 specific siRNA-transfected astrocyte cells. Thus, PKM2 also might negasitive regulate p27 following SCI and the repair process, and further influence the cyclin E/ CDK2 in cell cycle progression.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…17 In the current study, we found PKM2 could interact with p27, and decreased level of p27 in PKM2 specific siRNA-transfected astrocyte cells. Thus, PKM2 also might negasitive regulate p27 following SCI and the repair process, and further influence the cyclin E/ CDK2 in cell cycle progression.…”
Section: Discussionsupporting
confidence: 51%
“…p27 Kip1 (p27) is a key cell-cycle regulator, which negatively regulates cell cycle progression via inhibiting the cyclinE/CDK2 complexes directly. 17,18 The activity of p27 is controlled by its concentration, distribution among different cellular complexes, and its cellular location. 19,20 The final step in glycolysis is catalyzed by Pyruvate kinase (PK) via transferring the phosphate from phosphoenolpyruvate (PEP) to ADP, thereby generating pyruvate and ATP.…”
Section: Introductionmentioning
confidence: 99%
“…The p27 protein is structurally homologous to the p21 protein; p27 expression leads to the arrest of the cell cycle, and is increased by growth inhibition signals, while it is decreased by growth stimulating signals, leading to cell cycle progression (18).…”
mentioning
confidence: 99%
“…Fillies et al 38 reported that increased HIF-1 alpha expression was associated with good prognosis in early stage squamous cell carcinoma of the oral floor, but they speculated that expression of HIF-1 alpha is not hypoxia related but is due to alterations in oncogene or tumor suppressor genes. Therefore, we investigated the prognosis of patients with OSCC in stage I, II and stage III, IV, respectively, to investigate the different behavior of HIF-1 alpha expression between early stage OSCC and advanced stage OSCC in the present study.…”
Section: Pcna Immunohistochemistry and Labeling Indicesmentioning
confidence: 99%